2020
DOI: 10.1186/s12957-020-01922-8
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility and safety of complete laparoscopic extended right hemicolectomy with preservation of the ileocecal junction in right-transverse colon cancer

Abstract: Background: To evaluate the feasibility and safety of a new surgical method, complete laparoscopic extended right hemicolectomy with preservation of the ileocecal junction in right-transverse colon cancer. Methods: We retrospectively analyzed and compared the data of consecutive patients with right-transverse colon cancer who underwent complete laparoscopic extended right hemicolectomy with preservation of the ileocecal junction (n = 23) and conventional complete laparoscopic extended right hemicolectomy (n = … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It is also worth mentioning that ileocecal junction resection surgery might affect bowel movement, enteric bacteria and nutrition state [ 13 ]. According to Su et al [ 16 ], in comparison to conventional extended right hemicolectomy, the incidence of diarrhea was lower in ileocecal junction-preserved surgery ( p = 0.026). In addition to that, the defecation frequency was lower in this group on the 1st, 3rd, and 6th month post-operative ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth mentioning that ileocecal junction resection surgery might affect bowel movement, enteric bacteria and nutrition state [ 13 ]. According to Su et al [ 16 ], in comparison to conventional extended right hemicolectomy, the incidence of diarrhea was lower in ileocecal junction-preserved surgery ( p = 0.026). In addition to that, the defecation frequency was lower in this group on the 1st, 3rd, and 6th month post-operative ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…This nding suggests that it is not necessary to ligate both the lt-MCA and LCA in SFC [18,19]. In colon cancer, pericolic lymph nodes are present within 10 cm of the tumor, followed by the nodes along the next arterial arcade, centrally towards the SMA or IMA [14,[20][21][22][23]. Hohenberg et al suggested that it is important to ligate feeding arteries that ow within 10 cm of the tumor [10].…”
Section: Discussionmentioning
confidence: 99%